Kompetensi Pedagogik Guru Dalam Melaksanakan Penilaian Pembelajaran Di Sekolah Dasar - Ully, Mawaddatun; Badarudin, Badarudin; Juaini, Muhamad (Educatio, 2024)
This study reveals and analyzes in more depth and reveals various problems of teacher pedagogical competence in elementary schools in implementing learning and solving existing problems and alternative solutions that can be done to overcome the problems of teacher pedagogical competence, especially in elementary schools. The research approach used in this study is a qualitative approach. This research is aqualitative (naturalistic) research with a field research type. Based on the previous description, it can be concluded that 1) Problems of teacher pedagogical competence in learning include; a) media to be used in the learning process, b) minimal emotional stability and c) lack of teacher interest in research (sense academic research). 2) Implementation of the application of elementary school teacher pedagogical competence in implementing learning assessments that meet the criteria a) application of student characteristic assessments; (b) application of pedagogy based on mastery of learning theory and learning principles; (c) application of curriculum-based pedagogy; (d) application of pedagogy based on the implementation of learning; (e) application of pedagogy based on utilizing information and communication technology; (f) application of pedagogy based on effective, empathetic, and polite communication; (g) application of pedagogy based on assessment and evaluation of learning processes and outcomes; and (h) application of pedagogy based on utilization of assessment and evaluation results. 3) The impact of elementary school teachers' pedagogical competence in implementing learning assessment in elementary schools is that it can provide an overview of pedagogical competence, especially learning assessment, which must be possessed by teachers in order to achieve success in learning.